EFFECT OF ANTIPHOSPHOLIPID IN IRAQI WOMEN UNDERGOING ICSI TECHNIQUE: Received: 22nd March 2021; Revised: 02nd June 2021, 02nd July 2021, 15th July; Accepted: 06th August 2021 - AL-Sallami, Alaauldeen S. M; Al-Shimerty, Dhirgam F. Hassan (LIFE: International Journal of Health and Life-Sciences, 2021)
This study was conducted on 84 Iraqi women samples under the ICSI program. The sample was divided into two parts: intravenous blood section for WBC measurement and serum section for antiphospholipid (IgG & IgM) measurement, while hCG was used to indicate the success of ICSI and the presence or absence of pregnancy. The results showed a significant difference (p < 0.05) between the pregnancy failure group and the abortion group compared with the control group (pregnancy continuation) about the level of Antiphospholipid (IgG-IgM) and WBC. The current study found a positive relationship between the level of Antiphospholipid (IgG-IgM) and WBC of these two factors, concluded that both criteria may indicate one for the other in women who suffer from miscarriage and pregnancy failure after ICSI.